Histology and Morphology of The Epigonal Organ with Special Referance to the Lymphomyeloid System in Rhinobatos rhinobatos - Bircan-Yildirim, Yasemin; Cek, Sehriban; Basusta, Nuri; Atik, Esin (Central Fisheries Research Inst, 2011)
The present study is the first trial to describe the structure of the lymphomyeloid epigonal organ of the Rhinobatos rhinobatos. The morphological structure of the epigonal organ was similar in males and females and it was classified as stingray type. This organ possessed erythrocytes, thrombocytes, lymphocytes and two distinct types of granulocyts (eosinophils and neutrophils). Basophils were not detected in this study. Thrombocytes were variable in shape and lacked visible granules and some of them were spindle-shaped. Erythrocyte histology was similar to that previously described in birds, reptiles, amphibians, teleost and elasmobranchs. Granulocytes were probably stored within the lymphomyeloid epigonal organ and entered the circulation on maturation.
Rhinobathos rhinobathos'ta lenfomyeloid sisteme özel epigonal organın histolojisi ve morfolojisi
Keywords: Rhinobatos rhinobatos; epigonal organ; lymphomyeloid system; histology